Rekonstruksi Maqām Ruhani dalam Tasawuf al-Ghazālī: Analisis Kualitatif atas Iḥyā’ ‘Ulūm ad-Dīn - Ahmad Syahid; Muhammad Arwani; Isop Syafei; Izzuddin Musthafa (Journal of Education and Social Culture, 2025)
Sufism constitutes a central dimension of Islamic scholarship, focusing on inner spiritual cultivation through maqāmāt and aḥwāl as means of approaching Allah. Imam al-Ghazālī, through his seminal work Iḥyā’ ‘Ulūm ad-Dīn, plays a pivotal role by integrating Sufism, sharī‘ah, and ethics. Although widely influential, the conceptual construction of maqām rūḥānī in this work has not been systematically reconstructed using a qualitative textual approach. Prior studies have discussed maqām in Islamic psychotherapy, psychology of religion, and spiritual education, yet they rarely address its structural and dynamic dimensions within al-Ghazālī’s framework. This study adopts qualitative library research employing content analysis and contextual-hermeneutic interpretation of Iḥyā’ ‘Ulūm ad-Dīn. The findings indicate that al-Ghazālī’s concept of maqām rūḥānī is integrative, dynamic, and non-hierarchical, reflecting a continuous process of ethical and spiritual transformation connected to tazkiyat al-nafs. Its adaptive structure corresponds to the spiritual condition of the sālik, rendering it relevant for contemporary Islamic education spirituality.